A convergent modified HS-DY hybrid conjugate gradient method for unconstrained optimization problems. Issue 1 (2nd January 2019) - Mtagulwa, Peter; Kaelo, P.
Abstract: Conjugate gradient algorithm (method) is a very simple and powerful technique for solving large scale unconstrained optimization problems. In this paper a new modified hybrid conjugate gradient method, based on the work of Liu and Du [17] and Dong, Jiao and Chen [8], is proposed. We show that the proposed algorithm satisfies the descent condition and its global convergence is also established under the weak Wolfe-Powell line search conditions. The proposed algorithm is tested on a number of benchmark problems and the numerical results show that the proposed algorithm is very competitive.